Potensi Kulit Tuna (Thunnus sp.) sebagai Sumber Gelatin melalui Pretreatment Asam Kandis dan Ultrasonikasi - Khairannisa Khairannisa; Syamsi Aini (MASALIQ, 2026)
Although gelatin extraction from tuna skin has been widely studied, the use of asam kandis as a natural acid combined with ultrasonic bath assistance remains limited. This study aimed to determine the physicochemical characteristics and functional groups of tuna skin gelatin extracted using asam kandis and an ultrasonic bath. This study employed a quantitative approach with a laboratory experimental design. The extraction process included pretreatment using 0.1 M NaOH for 2 hours, soaking in an asam kandis solution at pH 2.4 for 1 hour, and extraction using an ultrasonic bath at 55 °C for 90 minutes. The data were analyzed through tests of yield, moisture content, ash content, fat content, pH, viscosity, and Fourier Transform Infrared (FTIR) analysis. The results showed that the gelatin produced had a yield of 12.45%, moisture content of 10.14%, ash content of 1.62%, fat content of 1.46%, pH of 6.51, and viscosity of 1.99 cP, thereby meeting gelatin quality standards. FTIR analysis identified characteristic gelatin absorption bands at wavenumbers of 3278 cm⁻¹ (Amide A), 1633 cm⁻¹ (Amide I), 1531 cm⁻¹ (Amide II), and 1243 cm⁻¹ (Amide III). These findings indicate that the combination of asam kandis and an ultrasonic bath can produce tuna skin gelatin with good physicochemical characteristics and has the potential to be developed as an alternative to commercial gelatin.